Correlation of goniometric and spinal level measurements of shoulder internal rotation - Kibler, W. B.; Zellers, B. (2002)
Correlation coefficients for two different measures of shoulder internal rotation-goniometric glenohumeral rotation in the scapular plane and achievement of a certain spinal level-were calculated for a cohort of 24 college tennis players. Measurements were taken from dominant and nondominant sides, and all measurements for each technique were made by the same examiner, according to established protocols. Correlation of spinal level with goniometric internal rotation was 0.157 for the dominant side, 0.038 for the nondominant side, and 0.092 for both sides. All of the values are not statistically significant, meaning that the tests are measuring two separate shoulder functions. These results indicate that testing spinal level is an inappropriate substitute for goniometric measurement of glenohumeral internal rotation. Possible confounding variables in the spinal level method of measurement include scapular winging, forearm pronation, wrist deviation, and thumb size and position. Changes in glenohumeral internal rotation have been associated with abnormal shoulder translations, decreased arm velocity, and extra loads on the elbow in the throwing athlete. Based on the results of this study, direct measurement of glenohumeral internal rotation should be done in the evaluation of shoulder function.